INVESTIGATING A TEACHER’S STRATEGIES TO TEACH ENGLISH DURING COVID 19 PERIOD - Maghfiratul Khasanah; Asfi Aniuranti; M.Happy Nur Tsani (Economics, Social, and Humanities Journal (Esochum), 2022)
Teaching strategy is a crucial element of teaching and learning process especially when students and teachers cannot meet directly due to the covid-19. Technology and internet access become essential to connect them, but for schools that do not have technology and internet access, it will be difficult to conduct the teaching and learning process. The condition appears in MA Al Ikhsan Beji where most of students stay in Islamic boarding school, and they are not allowed to bring their mobile phones. Therefore, this research focuses on the strategies used by the English teacher of MA Al Ikhsan Beji. This study was a descriptive quantitative research. The researchers employed interview sheet and questioner to gather the data. Then, the researchers analysed the data obtained through data coding, data reduction, data display, and drawing conclusion. This study revealed there were some strategies employed by the English teacher. The teacher used planning, drafting, and writing in teaching writing, and she also employed bottom up strategy to teach reading. Meanwhile, dialogue was the strategy for teaching speaking. In short, limited technology encountered by the teacher had been overcome by implementing several teaching strategies.